PENINGKATAN KOMPETENSI DAN PENGETAHUAN APOTEKER TERHADAP OBAT OFF LABEL MELALUI WORKSHOP AND TRAINING - Suharjono Suharjono; Mahardian Rahmadi; Chrismawan Ardianto; Arina Dery Puspitasari; Dewi Wara Shinta (Universitas Airlangga, 2018)
Drug information off label is not widely known and understood by health workers, both doctors and pharmacists. Prescribing drugs off label will also have an impact on ethical rules and drug costs, whether legal and can be covered by insurance. Therefore, there needs to be a continuing education activity for Pharmacists and health professionals to provide information and understanding of participants with the development of drugs off the label. This activity aims to improve the competencies of the participants, as well as understand the legal prescribing rules and as input for insurance and pharmaceutical regulations. The form of activities that will be carried out are workshops and training. The event was held for 2 days, 14-15 October 2018 at Graha Iptekdok, FKUA. There are 10 resource persons with 11 materials divided into 6 workshops, and 1 Micromedex training activity. This activity was attended by 383 participants and 5 invitations. Among the 383 participants, 55% were pharmacists working in hospitals, 30% were pharmacists working in pharmacies, and the rest were pharmacists working in industries, health centers, health services, and pharmacy students. Domicile participants come from various regions, with the largest percentage from Java. Based on the results of the questionnaire evaluation, the average material suitability assessment with participants’ needs was 8 out of 10. On the other hand, the material mastery by the speakers was also very good (8 out of 10). While in terms of the event, the average participant rated very well (7-9 of a scale of 10). A value of 7 is given to the parameters of room facilities. Seeing the enthusiasm of the participants of the Off Label Workshop andTraining in Community and Clinical Settings, the committee plans to follow up by holding a similar event to accommodate potential participants who cannot be accommodated in this event.AbstrakInformasi obat off label belum banyak diketahui dan dipahami oleh para tenaga kesehatan, baik dokter maupun apoteker. Peresepan obat off label juga akan berdampak pada aturan etik dan biaya obat, apakah legal dan bisakah ditanggung oleh asuransi. Oleh sebab itu, perlu adanya suatu kegiatan pendidikan berkelanjutan kepada para Apoteker dan profesi kesehatan untuk memberikan informasi dan pemahaman peserta dengan perkembangan obat off label. Kegiatan ini bertujuan untuk meningkatkan kompetensi para peserta, juga memahami aturan peresepan yang legal dan sebagai masukan untuk asuransi serta peraturan farmasi. Bentuk kegiatan yang akan dilakukan adalah workshop dan training. Acara dilakukan selama 2 hari, 14–15 Oktober 2018 di Graha Iptekdok, FKUA. Terdapat 10 narasumber dengan 11 materi yang dibagi dalam 6 workshop, dan 1 kegiatan pelatihan Micromedex. Kegiatan ini dihadiri oleh 383 peserta dan 5 undangan. Diantara 383 peserta, 55% merupakan apoteker yang bekerja di rumah sakit, 30% adalah apoteker yang bekerja di apotek, dan sisanya adalah apoteker yang bekerja di industri, puskesmas, dinas kesehatan, dan mahasiswa farmasi. Domisili peserta berasal dari berbagai daerah, dengan prosentase terbesar dari Jawa. Berdasarkan hasil evaluasi kuesioner, rata-rata penilaian kesesuaian materi dengan kebutuhan peserta adalah 8 dari skala 10. Selain itu, penguasaan materi oleh narasumber juga sangat baik (8 dari skala 10). Sedangkan dari segi acara, rata-rata peserta menilai sangat baik (7–9 dari skala 10). Nilai 7 diberikan pada parameter fasilitas ruangan. Melihat antusiasme dari peserta off Label Drugs Workshop and Training in Community and Clinical Settings, maka panitia berencana akan melakukan tindak lanjut dengan mengadakan acara yang serupa untuk mengakomodir calon peserta yang tidak dapat tertampung pada acara ini.